Higher risk of dementia in English older individuals who are overweight or obese. (23rd June 2020) - Ma, Yixuan; Ajnakina, Olesya; Steptoe, Andrew; Cadar, Dorina
Abstract: Background: Several risk factors contribute to dementia, but the role of obesity remains unclear. This study investigated whether increased body weight or central obesity were associated with a higher risk of developing dementia in a representative sample of older English adults. Methods: We studied 6582 participants from the English Longitudinal Study of Ageing (ELSA) who were aged ≥50 years and were dementia-free at baseline, that being either wave 1 (2002–2003) for study members who started at wave 1, or at either wave 2 (2004–2005) or 4 (2008–2009) for those who began the study as refreshment samples. Body mass index (BMI) was measured at baseline and categorized into normal weight (18.5–24.9 kg/m 2 ), overweight (25–29.9 kg/m 2 ) and obese (≥30 kg/m 2 ). Central obesity was defined as a waist circumference (WC) >88 cm for women and >102 cm for men. Cumulative incidence of dementia was ascertained based on physician-diagnosed dementia, an overall score >3.38 on the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) and Hospital Episodes Statistics (HES) data at every ELSA wave from baseline until wave 8 (2016–2017). Cox proportional hazards models were used to assess the association between baseline BMI levels or abdominal obesity in relation to dementia incidence during the mean follow-up period of 11 years. Results: From the overall sample, 6.9% ( n  = 453) of participants developed dementia during the follow-up period of maximum 15 years (2002–2017). Compared with participants with normal weight, those who were obese at baseline had an elevated risk of dementia incidence [hazard ratio (HR) = 1.34, 95% confidence interval (CI) 1.07–1.61] independent of sex, baseline age, apolipoprotein E-ε4 (APOE-ε4), education, physical activity, smoking and marital status. The relationship was slightly accentuated after additionally controlling for hypertension and diabetes (HR = 1.31, 95% CI 1.03–1.59). Women with central obesity had a 39% greater risk of dementia compared with non-central obese women (HR = 1.39, 95% CI 1.12–1.66). When compared with a normal BMI and WC group, the obese and high WC group had 28% (HR = 1.28, 95% CI 1.03–1.53) higher risk of dementia. Conclusions: Our results suggest that having an increased body weight or abdominal obesity are associated with increased dementia incidence. These findings have significant implications for dementia prevention and overall public health.